Towards real-time MRI-guided 3D localization of deforming targets for non-invasive cardiac radiosurgery. (25th October 2016) - Ipsen, S; Blanck, O; Lowther, N J; Liney, G P; Rai, R; Bode, F; Dunst, J; Schweikard, A; Keall, P J
Abstract: Radiosurgery to the pulmonary vein antrum in the left atrium (LA) has recently been proposed for non-invasive treatment of atrial fibrillation (AF). Precise real-time target localization during treatment is necessary due to complex respiratory and cardiac motion and high radiation doses. To determine the 3D position of the LA for motion compensation during radiosurgery, a tracking method based on orthogonal real-time MRI planes was developed for AF treatments with an MRI-guided radiotherapy system. Four healthy volunteers underwent cardiac MRI of the LA. Contractile motion was quantified on 3D LA models derived from 4D scans with 10 phases acquired in end-exhalation. Three localization strategies were developed and tested retrospectively on 2D real-time scans (sagittal, temporal resolution 100 ms, free breathing). The best-performing method was then used to measure 3D target positions in 2D–2D orthogonal planes (sagittal-coronal, temporal resolution 200–252 ms, free breathing) in 20 configurations of a digital phantom and in the volunteer data. The 3D target localization accuracy was quantified in the phantom and qualitatively assessed in the real data. Mean cardiac contraction was ⩽ 3.9 mm between maximum dilation and contraction but anisotropic. A template matching approach with two distinct template phases and ECG-based selection yielded the highest 2D accuracy of 1.2 mm. 3D target localization showed a mean error of 3.2 mm in the customized digital phantoms. Our algorithms were successfully applied to the 2D–2D volunteer data in which we measured a mean 3D LA motion extent of 16.5 mm (SI), 5.8 mm (AP) and 3.1 mm (LR). Real-time target localization on orthogonal MRI planes was successfully implemented for highly deformable targets treated in cardiac radiosurgery. The developed method measures target shifts caused by respiration and cardiac contraction. If the detected motion can be compensated accordingly, an MRI-guided radiotherapy system could potentially enable completely non-invasive treatment of AF.